2013
DOI: 10.1016/j.jvs.2013.05.091
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid aortic arch repair for complicated type B aortic dissection

Abstract: HAR in zone 1 and 2 appears a viable alternative to conventional aortic arch surgery in patients with complicated type B dissection. Stroke and endoleaks remain complications that need to be addressed. Treatment of type B aortic dissection with complete supra-aortic debranching and thoracic endovascular aortic repair in zone 0, however, is associated with high mortality, which might be reduced by improved technology using branched stent grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 19 publications
2
54
3
2
Order By: Relevance
“…Furthermore, especially in patients with dissection, repair of zone 0 might have a higher risk of technical failure or retrograde dissection. 12,22 The stroke rate was also remarkably high in our series (>10%). This might be a result of the highly diseased arch in our group of patients with elevated risk of embolization during wire or device manipulation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Furthermore, especially in patients with dissection, repair of zone 0 might have a higher risk of technical failure or retrograde dissection. 12,22 The stroke rate was also remarkably high in our series (>10%). This might be a result of the highly diseased arch in our group of patients with elevated risk of embolization during wire or device manipulation.…”
Section: Discussionsupporting
confidence: 51%
“…Nevertheless, there are few data available comparing limited hybrid reconstruction for zone 1 and zone 2 in short-and long-term durability. 9,10,[12][13][14] This study is a single-center, retrospective analysis of patients treated with hemiarch aortic hybrid procedures in zone 1 and zone 2 (zone 0 procedures are excluded).…”
mentioning
confidence: 99%
“…Hybrid repair has been introduced as a promising option to avoid open surgical procedures in such challenging anatomic configurations [3]. It can achieve effects similar to those of open surgical repair of thoracic aortic pathologic conditions, and meanwhile it reduces the use of cardiopulmonary bypass and circulatory arrest [4].…”
Section: Commentmentioning
confidence: 99%
“…The procedure was performed through an extrathoracic approach without median repeated sternotomy, cardiopulmonary bypass, or hypothermic circulatory arrest and mainly involved a simplified arch debranching technique. Compared with a conventional arch debranching technique, LSCA revascularization is indispensable when a dominant LVA originates from the LSCA [3,5]. Anatomic studies have reported that 60% of patients have a dominant LVA, with the right vertebral artery being smaller, atretic, or completely absent.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation